2015
DOI: 10.17795/ajnpp-31238
|View full text |Cite
|
Sign up to set email alerts
|

Histamine Potentiates Cyclosomatostatin-Induced Catalepsy in Old Rats

Abstract: Background:The decreased level of somatostatin and increased level of histamine are detected in the Parkinsonian brain. In old Wistar rats, the brain somatostatin deficiency can initiate catalepsy that suggests the pathogenic significance of this abnormality in Parkinson's disease (PD). The ability of histamine to affect the somatostatin deficiency action is not studied. Objectives: The current study aimed to examine if histamine alters the cataleptogenic activity of the brain somatostatin deficiency in Wistar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
7
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 22 publications
2
7
0
Order By: Relevance
“…One of the iPD-associated brain abnormalities is a fall in somatostatin levels (for refs., see [8,9]). These changes may be of pathogenic importance as somatostatin can stimulate dopaminergic neurotransmission [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the iPD-associated brain abnormalities is a fall in somatostatin levels (for refs., see [8,9]). These changes may be of pathogenic importance as somatostatin can stimulate dopaminergic neurotransmission [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…We recently simulated a decrease in brain somatostatin activity in Wistar rats [8,9,13] using intracerebral injections of cyclosomatostatin (cS), an antagonist of somatostatin receptors [14]. It has been found that cS induces cataleptic response.…”
Section: Introductionmentioning
confidence: 99%
“…One of the iPD-associated brain abnormalities is a fall in somatostatin levels (for refs., see [8,9]). These changes may be of pathogenic importance as somatostatin can stimulate dopaminergic neurotransmission [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…We recently simulated a decrease in brain somatostatin activity in Wistar rats [8,9,13] using intracerebral injections of cyclosomatostatin (cS), an antagonist of somatostatin receptors [14]. It has been found that cS induces cataleptic response.…”
Section: Introductionmentioning
confidence: 99%
“…One of the IPD-associated abnormalities is dropping the brain levels of somatostatin [7]. These changes may be of pathogenic importance as somatostatin can modulate dopaminergic neurotransmission.…”
Section: Introductionmentioning
confidence: 99%